Double-blind, randomized, placebo-controlled study of trofinetide in pediatric Rett syndrome. (16th April 2019) - Glaze, Daniel G.; Neul, Jeffrey L.; Kaufmann, Walter E.; Berry-Kravis, Elizabeth; Condon, Sean; Stoms, George; Oosterholt, Sean; Della Pasqua, Oscar; Glass, Larry; Jones, Nancy E.; Percy, Alan K.; Glaze, Daniel G.; et al.
Abstract : Objective: To determine safety, tolerability, and pharmacokinetics of trofinetide and evaluate its efficacy in female children/adolescents with Rett syndrome (RTT), a debilitating neurodevelopmental condition for which no pharmacotherapies directed at core features are available. Methods: This was a phase 2, multicenter, double-blind, placebo-controlled, parallel-group study, in which safety/tolerability, pharmacokinetics, and clinical response to trofinetide were characterized in 82 children/adolescents with RTT, aged 5 to 15 years. Sixty-two participants were randomized 1:1:1:1 to receive placebo twice a day (bid) for 14 days, followed by placebo, 50, 100, or 200 mg/kg bid of trofinetide for 42 days. Following blinded safety data review, 20 additional participants were randomized 1:1 to the 200 mg/kg or placebo bid groups. Safety assessments included adverse events, clinical laboratory tests, physical examinations, and concomitant medications. Clinician- and caregiver-based efficacy measurements assessed clinically relevant, phenotypic dimensions of impairment of RTT. Results: All dose levels were well tolerated and generally safe. Trofinetide at 200 mg/kg bid showed statistically significant and clinically relevant improvements relative to placebo on the Rett Syndrome Behaviour Questionnaire, RTT-Clinician Domain Specific Concerns–Visual Analog Scale, and Clinical Global Impression Scale–Improvement. Exploratory analyses suggested that observed changes correlated with trofinetide exposure. Conclusion: These results, together with those from a previous adolescent/adult trial, indicate trofinetide's potential for treating core RTT symptoms and support further trials. Classification of evidence: This study provides Class I evidence that for children/adolescents with RTT, trofinetide was safe, well-tolerated, and demonstrated improvement over placebo at 200 mg/kg bid in functionally important dimensions of RTT.